Penerapan Konsep Matematika dalam Pengelolaan Keuangan Rumah Tangga di Desa Penfui Timur - Jusrry Rosalina Pahnael; Robertus Dole Guntur; Maria Lobo; Maria Agustina Kleden; Astri Atti; Mira Wadu; Brian Juned Septory; Sulche Ifone Nafi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Nusa Cendana, 2025)
Abstract Women in Penfui Timur Village as household financial managers mostly only depend on their husband's income which has been used or deducted by the Bank or cooperative because it is used to build a house or other business. However, some of them lack creativity in increasing other income or investing their husband's money in the form of small businesses or investments. Therefore, mathematics lecturers in collaboration with economics lecturers will provide enlightenment in the form of delivering materials and exercises and sharing experiences in terms of managing household finances fairly, wisely, and creatively innovatively. Our hope is that after receiving learning and sharing experiences from competent lecturers in mathematics and economics, women in Penfui Timur Village will be strengthened and have ideas in managing household finances efficiently and fairly and be creative in building alternative household businesses that of course see the market share to improve the economy in the home. With the aim that no family is lacking in material so that the next generation of the nation can go to school and have creativity with good nutritional value in order to achieve intelligence for all Indonesian people because they have parents who are diligent, creative, fair and wise in managing finances as a whole. Keywords: Mathematical concepts, Finance, Household, Creative, Entrepreneurship